Using the Imitating Models Techniques on Insya Teaching for Improving the Studentâs Writing Ability in Thesis - Nurbayan, Yayan (EDUCARE, 2011)
ABSTRACT: Writing skills is one of the skills of the four language competences that must be owned by each learner language. The researchs data show that student writing skills in thesis examined ten samples of 30% error rate is still high. This amount includes the category of very many, because they have received coaching from two tutors. This phenomenon has encouraged researchers to conduct research on learning to write through the technique of imitating models. The method used in this study was quasi experiment by taking a sample of university students majoring in Arabic language education as many as 27 people. Data analysis used descriptive qualitative. The results of this research are: (1) Learning to write by using a technique modeled requires good planning, ranging from the selection of instructional materials that can serve as a model to be emulated by students; (2) The technique of imitating models of the courses conducted by following the nine steps; (3) Learning to write or âinsyaâ by using the technique of imitating the model has improved the students ability in writing a âfaqrahâ or paragraph and âkitabah hurriyahâ or free text. This can be seen from the significant difference between the pretest conducted before the treatment begins with posttest results conducted after the study conducted; and (4) Ability to write âfaqrahâ and âkitabah hurriyahâ is the basic ability for someone to be able to write papers, books, reports, and other writings. KEY WORDS: Imitating models, techniques of âinsyaâ (writing), making âfaqrahâ (paragraph) and âkitabah hurriyahâ (free text), and studentsâ competences.About the Author: Dr. H. Yayan Nurbayan is a Lecturer at the Department of Arabic Language Education, Faculty of Arts and Language Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: anti.bandang@gmail.comHow to cite this article? Nurbayan, Yayan. (2011). âUsing the Imitating Models Techniques on Insya Teaching for Improving the Studentâs Writing Ability in Thesisâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.99-106. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 23, 2011); Revised (July 27, 2011); and Published (August 17, 2011).